Rola rozwiązań e-biznesowych w nowoczesnym przedsiębiorstwie na przykładzie firmy Wiśniowski - Baran, Marcin (My University, 2015)
Celem pracy było przedstawienie teoretycznych aspektów e-biznesu oraz jego znaczenia w polskich przedsiębiorstwach. Dokonano charakterystyki firmy oraz przybliżono rozwiązania e-biznesowe stosowane w firmie Wiśniowski w Wielogłowach. Praca zawiera również analizę wyników badań przeprowadzonych wśród kontrahentów firmy Wiśniowski, gdzie zbadany został wpływ oraz wykorzystanie e-biznesu.

The primary goal of the work was presentation of theoretical aspects of the e-business and its importance in Polish enterprises. There have been brought closer to the characteristics of the company and e-business solutions used in the Wiśniowski company located in Wielogłowy. The work also includes an analysis of the results of research carried out among Wiśniowski contractors, where there was examined the impact and use of e-business.
The role of e-business solutions in a modern enterprise on the example of Wiśniowski company
Keywords: e-biznes; biznes elektroniczny; e-commerce; B2B; internet; e-usługi; e-business; electronic business; B2B; Wisniowski; e-services